A115 CLINICAL, RADIOGRAPHIC, AND ENDOSCOPIC REMISSION WITH VEDOLIZUMAB TREATMENT IN CROHN'S DISEASE. (1st March 2018) - Kotze, P; Ma, C; Almutairdi, A; Al-Darmaki, A; Devlin, S; Kaplan, G G; Seow, C; Novak, K L; Lu, C; Ferraz, J; Stewart, M J; Buresi, M c; et al.
Abstract: Background: Vedolizumab is a gut-specific alpha-4-beta-7 integrin antagonist that has demonstrated efficacy in induction and maintenance of clinical response and remission in Crohn's disease randomized controlled trials. Aims: To evaluate the symptomatic and objective response and remission rates achieved with vedolizumab therapy in Crohn's disease in the real-world setting. Methods: A retrospective cohort study was performed at the University of Calgary of adult (≥18 years) CD patients receiving vedolizumab induction between 2012 and 2017. All patients received standard induction therapy with vedolizumab 300mg IV at weeks 0, 2, and 6 and were subsequently advanced onto a scheduled maintenance vedolizumab IV regimen. The primary outcome was achievement of clinical or objective remission at 3, 6, and 12 months after induction. Clinical remission was defined by complete absence of symptoms and no need for corticosteroids. Objective remission was defined by achievement of steroid-free endoscopic mucosal healing or complete normalization of radiographic appearance on contrast-enhanced ultrasound or CT/MR enterography. Results: We identified 122 CD patients treated with vedolizumab. Mean follow-up was 43.4 weeks (SD 30.8 weeks). 68.9% (84/122) of patients had previously failed anti-TNF therapy; 18.9% (23/122) of patients had failed at least three previous biologic therapies. Steroid-free clinical remission at 3 months, 6 months, and 12 months was 19.8% (22/111), 22.1% (21/95), and 22.1% (15/68), respectively. Steroid-free objective remission occurred in 11.5% (6/52), 21.2% (14/66), and 18.9% (7/37) patients at 3, 6, and 12 months, respectively. Mucosal healing on endoscopy was achieved by 22.2% (6/27), 33.3% (14/42), and 25.9% (7/27) of patients at 3, 6, and 12 months, respectively. Thirty-three patients (27.0%) required dose escalation during maintenance therapy to 300mg IV every 4 weeks; 23 patients required dose escalation to optimize primary response and 10 patients required dose escalation for secondary loss of response. An adverse event was reported in 35 patients (28.7%). The most common adverse events were infections (16/122, 6.6%) and infusion reactions (8/122, 6.6%). Serious adverse events requiring drug discontinuation or hospitalization were reported in 8 patients (6.6%). Two deaths occurred in the cohort: one patient developed cholangiocarcinoma in the context of pre-existing primary sclerosing cholangitis and a second patient died from metastatic renal cell carcinoma which had been diagnosed prior to vedolizumab. Conclusions: In this cohort of patients with highly refractory CD, vedolizumab was effective for inducing steroid-free clinical, endoscopic, and radiographic remission. Funding Agencies: None